1996
DOI: 10.1016/0014-5793(96)00277-3
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of a novel human RNA polymerase II subunit downregulated by doxorubicin: new potential mechanisms of drug related toxicity

Abstract: Using the differential display PCR method, we have isolated an mRNA downregulated in doxorubicin resistant human cell lines. The full length cDNA clone was identified as the human homologue of yeast RPBll subunit of RNA polymerase II. Northern blot analysis of normal tissues detected a particularly high expression of RPBll mRNA in heart and skeletal muscle. Reduction of this mRNA expression was observed in all the cell fines tested after drug treatment and was paralleled by a similar decrease of the protein le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 18 publications
2
41
0
Order By: Relevance
“…The rabbit polyclonal antibodies against human RPB11 and RPB3 have been described previously (Fanciulli et al, 1996;Corbi et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rabbit polyclonal antibodies against human RPB11 and RPB3 have been described previously (Fanciulli et al, 1996;Corbi et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…We found that RPB11 and RPB3 are expressed at high levels in adult human skeletal muscle and heart (Fanciulli et al, 1996;Fanciulli et al, 1998), and that RPB3 expression is regulated during murine C2C7 myoblast differentiation (Corbi et al, 2002). In addition, the involvement of RPB3 in tissue-specific transcription was demonstrated by its direct contact with transcription factors including ATF4 (a member of the ATF/CREB family) and Myogenin (a member of the MyoD gene family) (De Angelis et al, 2003;Corbi et al, 2002).…”
mentioning
confidence: 90%
“…As determined by gene ontology analysis, our radiation-induced 30 gene signature was significantly enriched for genes involved in pyruvate metabolism, generation of precursor metabolites and energy, suggesting that tumors most sensitive to chemotherapy are those with highest metabolic activity, consistent with the known mechanisms of action of several chemotherapeutics used in the datasets we analyzed, including doxorubicin and capecitabine (47)(48)(49)(50)(51)(52)(53). Genes composing our 30 gene signature include lactate dehydrogenase B (LDHB), which is a subunit of the lactate dehydrogenase enzyme, the key glycolytic enzyme catalyzing formation of lactic acid from pyruvate.…”
Section: Discussionmentioning
confidence: 58%
“…The major disadvantage, however, is that increased physical protection is required. 33 P is a viable alternative because it combines the advantages of both 35 S and 32 P and is more sensitive (139). A 1-Ci portion of 33 P allows the same sensitivity and resolution as 5 Ci of 35 S, thus making it cost-effective (76).…”
Section: Modificationsmentioning
confidence: 99%
“…The potential applications in medical mycology are readily apparent. One approach is to treat sensitive and resistant cells with a drug and then analyze them by DDRT-PCR (33). The difference between resistant and sensitive cells may also be analyzed in the absence of drug in order to provide insight into why a cell is sensitive or resistant to drug action (72).…”
Section: Drug Resistance and Targets For Drugsmentioning
confidence: 99%